Impossible Joyce : Finnegans wakes - O'Neill, Patrick, 1945- (University of Toronto Press, 2013)
James Joyce's Finnegans Wake has repeatedly been declared to be entirely untranslatable. Nonetheless, it has been translated, transposed, or transcreated into a surprising variety of languages - including complete renditions in French, German,